Sadari Anemia Dan Tablet Tambah Darah Pada Remaja Putri Dengan Pemanfaatan Media Sosial Dalam Promosi Kesehatan - Damai Ira Saraswati (Jurnal Kesehatan Indonesia, 2025)
Anemia is a common health issue among adolescent girls, affecting their quality of life and developmental potential. One effective strategy to address this problem is through accessible and engaging health education. This study aimed to evaluate the effectiveness of social media—particularly Instagram—as a health promotion platform to improve knowledge about anemia and iron supplementation (TTD) among adolescent girls. A pre-experimental one group pretest–posttest design was used, involving 70 participants who watched a 112-second educational video uploaded to the Instagram account @apotek.optimafarma. The Wilcoxon Signed-Rank Test revealed a significant increase in knowledge after the intervention (p < 0.05). The McNemar test also indicated significant changes in several aspects of knowledge, particularly regarding general understanding of anemia, its symptoms, causes, and iron tablet usage rules. These findings suggest that video-based educational content on social media can be an effective and inclusive strategy for health promotion targeting adolescent girls. Social media has proven to be a powerful channel for engaging young audiences with informative and appealing health messages tailored to their digital habits.